Characteristics of Chinese Petroleum Geology Geological Features and Exploration Cases of Stratigraphic, Foreland and Deep Formation Traps - Jia, Chengzao (Advanced Topics in Science and Technology in China, 2012)
"Characteristics of Chinese Petroleum Geology: Geological Features and Exploration Cases of Stratigraphic, Foreland and Deep Formation Traps" systematically presents the progress made in petroleum geology in China and highlights the latest advances and achievements in oil/gas exploration and research, especially in stratigraphic, foreland and deep formation traps. The book is intended for researchers, practitioners and students working in petroleum geology, and is also an authoritative reference work for foreign petroleum exploration experts who want to learn more about this field in China. As President of the Chinese Petroleum Society, former Vice-President of PetroChina Company Limited, and Academician of the Chinese Academy of Sciences, Dr. Chengzao Jia has been engaged in geological research for 30 years and in oil/gas exploration for more than 20 years.  .